Virtual Collaboration for a Distributed Enterprise - Cordova, Amado (RAND Corporation, 2013)
The geographic diversity of many military enterprises, their partners, and their customers has made virtual collaboration vital to their daily operations. However, virtual collaboration can pose challenges to effective team communication, as well as building cohesiveness and trust among team members. This report addresses these challenges through an assessment of three modes of virtual collaboration: computer-mediated communication, audioconferencing, and videoconferencing.